The development of the modern ideas of Islamic architecture in the modern Malaysia - Mohd. Rasdi, Mohd. Tajuddin; Syed Ariffin, Syed Ahmad Iskandar (Faculty of Built Enviroment, 2008)
The research aims to document and analyze the various thoughts and ideas of Islamic Architecture in the modem era from 1950 - 2000 existing in Malaysia. It is hoped that from this research the present and future design and ideas o f Islamic Architecture can be better articulated and developed specifically for Malaysia. The report comprises of four main parts. The first part examines the issues and problems stemming from lack of documentation and discourses on the ideas, theories and philosophies in the present practices of creating buildings deemed to be ‘Islamic’ or those referred to as Islamic Architecture in the Nusantara and the world. The second part of the report documents the various thoughts and ideas of Islamic Architecture in the world. The third part documents the ideas and thoughts on Islamic Architecture in Malaysia from 1950 to 2000. The last part attempts to relate the influence of global ideas of Islamic Architecture on the ones in Malaysia. It is hoped that this research will help create amore meaningful and integrated idea of Islamic Architecture for the future.